Time trend, prevalence and factors affecting place of delivery in rural area: a comparative study among two sub centers in field practice area of tertiary care center, Aurangabad, Maharashtra - Nakel, Mahavir P.; Gattani, Prakash L. (International Journal Of Community Medicine And Public Health, 2020)
Background: In the developing world, even today, perhaps delivery is the commonest event where life and death stand side by side for both, the expectant mother and her forthcoming newborn. India being second most populous country in the world, women and pre-school children constitute about one third of total population; any neglect or delay in care can adversely affect the wanted outcome. The aim of the study was to assess factors affecting institutional and home delivery in rural areas under field practice area of tertiary care center in Aurangabad city. The objectives of the study were as follows: to estimate the prevalence of home and hospital delivery in rural area and to study and analyze the factors affecting place of delivery i.e. home or hospital Methods: Present study was undertaken in the two sub centers under one of the primary health cares in field practice area under tertiary care hospital in Aurangabad city. A total of 659 respondent women were interviewed to collect information regarding first and last delivery. Results: Total 58.27% women were delivered in private hospitals and only 18.66% delivered in Government institutions while prevalence of Home delivery was 23.06%. Conclusions: Early antenatal care (ANC) registration from the first pregnancy of the women with recommended visits should be encouraged since ANC registration has greater influence in selection of place of delivery.